2022
DOI: 10.1093/ijnp/pyac068
|View full text |Cite
|
Sign up to set email alerts
|

M6A RNA Methylation-Based Epitranscriptomic Modifications in Plasticity-Related Genes via miR-124-C/EBPα-FTO-Transcriptional Axis in the Hippocampus of Learned Helplessness Rats

Abstract: Background Impaired synaptic plasticity has been linked to dynamic gene regulatory network changes. Recently, gene regulation has been introduced with the emerging concept of unique m 6A-based reversible transcript methylation. In this study, we tested whether m 6A RNA methylation may potentially serve as a link between the stressful insults and altered expression of plasticity-related genes. Methods Expression of plasticity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 85 publications
0
1
0
Order By: Relevance
“…The copyright holder for this preprint this version posted January 8, 2024. ; https://doi.org/10.1101/2024.01.08.574593 doi: bioRxiv preprint a positive correlation of m 6 A methylation and the methyltransferase Mettl3 levels with ability of contextual fear discrimination and demonstrated that expression of Mettl3 in hippocampal glutamatergic neurons is crucial for this type of learning and memory (Chang et al, 2022). In learned helpless rats the expression of several so-called plasticity genes in hippocampus was downregulated along with enrichment in their m 6 A methylation (Roy et al, 2022). In summary, RNA m 6 A methylation serves as a crucial regulation mechanism at the epitranscriptomic level to shape synaptic plasticity and behaviour (Malovic and Pandey, 2023) and involvement of RNA m 6 A methylation appears in multiple behavioural conditions relevant to anxiety, but so far evidence for a role of m 6 A methylation has remained correlational.…”
Section: Introductionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted January 8, 2024. ; https://doi.org/10.1101/2024.01.08.574593 doi: bioRxiv preprint a positive correlation of m 6 A methylation and the methyltransferase Mettl3 levels with ability of contextual fear discrimination and demonstrated that expression of Mettl3 in hippocampal glutamatergic neurons is crucial for this type of learning and memory (Chang et al, 2022). In learned helpless rats the expression of several so-called plasticity genes in hippocampus was downregulated along with enrichment in their m 6 A methylation (Roy et al, 2022). In summary, RNA m 6 A methylation serves as a crucial regulation mechanism at the epitranscriptomic level to shape synaptic plasticity and behaviour (Malovic and Pandey, 2023) and involvement of RNA m 6 A methylation appears in multiple behavioural conditions relevant to anxiety, but so far evidence for a role of m 6 A methylation has remained correlational.…”
Section: Introductionmentioning
confidence: 99%